The Pedagogical Competence Of Arabic Language Teachers In Teaching Blind Students/ الكفاءة التربوية لمعلم اللغة العربية في تعليم التلاميذ المكفوفين - Purwaningsih, Candra (UIN Raden Mas Said Surakarta, 2020)
This study aims to examine the competence of Arabic teachers in teaching blind students. Learning for the visually impaired certainly requires special competencies for teachers so that students get like other students. The approach used in this research is descriptive qualitative. The results of this study indicate that several competencies must be possessed by Arabic language teachers, especially in teaching blind students, including preparation, implementation, and evaluation. In the preparation contained in the lesson plan, there is no lesson plan specifically intended for blind students, but in the implementation and evaluation of learning the teacher uses a special strategy in teaching blind students.